Kinetic Spectrophotometic Determination of Trace Amounts of Copper Based on its Catalytic Effect on the Reaction of DBC-Arsenazo and Hydrogen Peroxide - Song, Bo; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2010)
A new catalytic-kinetic spectrophotometric method is proposed for the determination of copper, based on the catalytic effect of copper(II) on the oxidation of dibromo-p-chloro-arsenazo (DBC-ASA) by hydrogen peroxide in the acid medium of 1.2 × 10-3 mol/L H3PO4. The copper can be determined spectrophotometrically by measuring the decrease in the absorbance of DBC-arsenazo at the wavelength of 514 nm using the fix-time method. The optimum reaction conditions are as follows: 1.2 × 10-3 mol/L of H3PO4 of medium, 4.0 × 10-5 mol/L of DBC-arsenazo, 0.18 mol/L of H2O2, reaction temperature 100 ºC and reaction time 8 min. The linear range of the method for the determination of copper(II) is between 0.1-1.2 μg in 25 mL of solution and the limit of detection is 3.2 ng/mL. The method has been successfully applied to the determination of copper in water samples.